PENGEMBANGAN MEDIA PEMBELAJARAN JEGOLAN UNTUK MENINGKATKAN MINAT BELAJAR IPA SISWA KELAS V SDN CIJENGKOL 02 - Selvi Aryani Damayanti; Awalina Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on the results of observations and interviews with the homeroom teacher of grade V, it is known that low student learning interest occurs due to the lack of learning media in the student learning process, the use of learning media is needed to attract student learning interest, especially in science learning on the material of animal classification based on their food types. This study aims to increase student learning interest. This study uses a type of development research using the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The feasibility test was carried out by three expert validations, namely media experts obtained a score of 83%, language experts obtained a score of 96%, and material experts obtained a score of 90%. The validation results from the three experts showed the feasibility of the media to be tested. Then the effectiveness test using a learning interest questionnaire from the results of small group trials obtained a score of 87.7% and a large group trial obtained a percentage of 85.6% with very effective criteria. While the teacher response questionnaire obtained a score of 95.3% and the student response questionnaire obtained a score of 89.3% with very good criteria. Based on the results of the study, it can be concluded that the Jegolan learning media can increase student learning interest.